1996
DOI: 10.1016/0735-1097(96)00089-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypomagnesemia: Characterization of a model of sudden cardiac death

Abstract: In this model, magnesium deficiency results in sudden cardiac death. The presence of startle induction of sudden death preceded by seizures suggests that sudden cardiac death results from a neurologic trigger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 25 publications
2
32
0
Order By: Relevance
“…9,11 Mg deficiency contributes to the pathogenesis of several cardiovascular diseases, eg, hypertension, 12 vasospastic angina, 13 ventricular arrhythmia, 14 and mitral valve prolapse. 15 Recently, Fiset et al 16 reported a high incidence of sudden death in Mg-deficient rats, and this result is consistent with epidemiological reports of a high incidence of sudden death in areas with low levels of Mg in drinking water 17 and also with clinical reports that hypomagnesemia is frequently observed in patients with heart failure in whom sudden death occurs. 14,18 Animal studies have suggested that there are 2 mechanisms of sudden death related to Mg deficiency: arrhythmogenesis and coronary vasospasm.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…9,11 Mg deficiency contributes to the pathogenesis of several cardiovascular diseases, eg, hypertension, 12 vasospastic angina, 13 ventricular arrhythmia, 14 and mitral valve prolapse. 15 Recently, Fiset et al 16 reported a high incidence of sudden death in Mg-deficient rats, and this result is consistent with epidemiological reports of a high incidence of sudden death in areas with low levels of Mg in drinking water 17 and also with clinical reports that hypomagnesemia is frequently observed in patients with heart failure in whom sudden death occurs. 14,18 Animal studies have suggested that there are 2 mechanisms of sudden death related to Mg deficiency: arrhythmogenesis and coronary vasospasm.…”
supporting
confidence: 74%
“…1,4,5,19 Moreover, the effect of Mg deficiency on the autonomic nervous system may act as a neurogenic trigger of a fatal event. Fiset et al 16 reported that fatal arrhythmia occurred after seizures in Mg-deficient rats, whereas there was a small effect on repolarization of ventricular myocytes. The authors implied that the abnormal response of the autonomic nervous system to auditory stress led to a fatal event.…”
mentioning
confidence: 99%
“…Results found that 80% of the hypomagnesaemia rats suffered -episodes of bradycardia and tachycardia compared to the control group in which 0% showed any cardiac adversity (Fiset et al, 1996). As well as this, 36% of rats in the hypomagneseamic group suffered sudden unexpected asystolic death compared to 0% in the control group (Fiset et al, 1996). In a study by Yusuf et al, tachycardia was the prime manifestation of Mg depletion in experimental animals followed by bradycardia (Afus et al, 2001).…”
Section: Hypomagnesaemia Induced By Cisplatin and Its Role In Cardiotmentioning
confidence: 99%
“…In a study conducted by Fiset et al, the correlation between hypomagnesaemia and cardiac death was studied in rats (Fiset et al, 1996). Results found that 80% of the hypomagnesaemia rats suffered -episodes of bradycardia and tachycardia compared to the control group in which 0% showed any cardiac adversity (Fiset et al, 1996). As well as this, 36% of rats in the hypomagneseamic group suffered sudden unexpected asystolic death compared to 0% in the control group (Fiset et al, 1996).…”
Section: Hypomagnesaemia Induced By Cisplatin and Its Role In Cardiotmentioning
confidence: 99%
See 1 more Smart Citation